Urbanization, Inequality, and Race: Socio-spatial Segregation and Territories of Exclusion - Benini, Sandra Medina; Godoy, Jeane Aparecida Rombi de; Silva, Allan Leon Casemiro da; Palmisano, Angelo (National Journal of City Management, 2025)
Objective: To analyze socio-spatial segregation in Brazilian cities based on the understanding of structural racism as a constitutive element of the production of urban space, demonstrating how urbanization has historically been organized in a racialized manner—particularly in the post-abolition period—and how this logic persists in contemporary contexts.Methodology: The study adopts a qualitative, deductive approach grounded in a critical theoretical essay. The analysis articulates frameworks from structural racism theory, the coloniality of power, and critical urban studies, in dialogue with documentary analysis of public policies and secondary data from official sources, such as the Brazilian Institute of Geography and Statistics (IBGE), used interpretively to demonstrate patterns of racial inequality in urban space.Originality/Relevance: The article contributes to urban studies by repositioning race as a central analytical category in the interpretation of socio-spatial segregation, confronting the erasure promoted by the ideology of racial mixing (mestiçagem) and by deracialized urban planning approaches. The study advances by demonstrating that the city is not merely a reflection, but an active instrument in the reproduction of racial inequalities, addressing a persistent theoretical gap in Brazilian urban literature.Results: The analysis shows that socio-spatial segregation in Brazil constitutes a historical and institutionalized expression of structural racism, manifested in the unequal distribution of infrastructure, urban services, mobility, and environmental protection. It reveals that urban planning practices, public policies, and real estate valorization dynamics operate in racialized ways, reinforcing the territorial marginalization of Black and peripheral populations.Theoretical/Methodological Contributions: The study strengthens the articulation between critical urban theory, structural racism, and coloniality, contributing to the understanding of segregation as a systemic and adaptive phenomenon. Methodologically, it reaffirms the relevance of the theoretical essay as an analytical tool for unveiling structural mechanisms of exclusion often obscured by technocratic approaches.Social and Environmental Contributions: By making explicit the connections between structural racism, urban segregation, and environmental vulnerability, the article supports debates on territorial justice and anti-racist urban policies. The findings reinforce the need for public policies oriented toward historical reparation, territorial redistribution, and the reduction of socio-environmental inequalities that disproportionately affect Black populations in Brazilian cities.
Keywords: Structural racism; Socio-spatial segregation; Brazilian urbanization